A broadband all-textile wearable MIMO antenna for wireless telecommunication/medical applications. Issue 12 (2nd December 2021) - Khajeh-Khalili, Farzad
Abstract: In this article, a novel wearable and broadband multiple-input and multiple-output (MIMO) antenna is designed for use in several wireless telecommunication/medical systems. In this antenna, two rectangular patches made of cotton fabric (CF) with a dielectric constant equal to 2.23 and a substrate made of a standard felt (SF) with a dielectric constant of 1.3 are employed. The use of two types of flexible and wearable dielectric instead of metal has increased the bandwidth by 7 GHz compared to the microstrip sample. The dimensions of the proposed antenna are equal to 54 × 36 × 2.5 mm 3 at 5 GHz. To prove the accuracy of the designs and simulations, the proposed MIMO antenna was fabricated and the measured results are reported. A good agreement was observed between the results of simulation and measurement. The frequency range covered by the proposed MIMO antenna is 1.1–8.6 GHz. Also, the maximum measured gain is equal to 8 dB at 5.5 GHz. Wearability, small size, simple design, low cost, and suitable gain, are among the advantages of the proposed wearable MIMO antenna.